The Effectiveness of Malcolm’s Modeling Based On KWL Thinking Strategy towards The Problem Solving Skills - Johan, Arno; Suyitno, Amin; Mashuri, Mashuri (Unnes Journal of Mathematics Education, 2017)
The learning model that can be implemented to improve problem solving skills is Malcolm’s Modeling. The objectives of this research were (1) to measure problem solving skill of the students who was taught by Malcom’s modeling based on KWL thinking strategy towards the minimum criteria scores; (2) to compare the students on problem solving skill who received Malcom’s Modeling based on KWL Thinking Strategy and expository learning model in the chapter of Scientific Notation. The population of this research were the students of seventh grade in Tainan Municipal Jincheng Junior High School in the academic year of 2016/2017. By simple random sampling technique, class 705 was selected as the experiment class and class 711 was selected as the control class. The data were collected by using some instruments, they were test and documentation. Data analysis used SPSS software and excel for t-test and proportion test. The results of the research showed that : (1) Malcom’s modeling based on KWL thinking strategy gained good result to the scores of the students; (2) the problem solving skill of the students who received Malcom’s Modeling using KWL Thinking Strategy was better than that skill of the students who received expository learning model.